Eye care skills [ presentations for physicians and other health care professionals - Johns, Karla J. (American Academy of Ophthalmology, 2009)
Designed to be a tool to create educationals and training presentations for nonophthalmic physicians, residents, and allied health personnel. More than 500 clinical images and text slides that can be used and adapted to create your own presentations